Reduced R2′ in multiple sclerosis normal appearing white matter and lesions may reflect decreased myelin and iron content. Issue 8 (23rd May 2012) - Paling, David; Tozer, Daniel; Wheeler-Kingshott, Claudia; Kapoor, R; Miller, David H; Golay, Xavier
Abstract : Background: R2 ′ is an MRI measure of microscopic magnetic field inhomogeneity, and is increased by the paramagnetic effect of iron and the diamagnetic effect of myelin. R2 ′ may detect features of multiple sclerosis (MS) not evident with conventional MRI. Methods: Multiecho T2 and T2 * weighted sequences were obtained from 21 healthy controls (nine men, 12 women; mean age 36 years) and 28 MS patients (seven men, 21 women; 18 relapsing remitting, 10 secondary progressive; mean age 42 years). T2 and T2 * relaxation time maps were created from the multiecho sequences, and R2 ′ maps were created using the formula R2 ′ = R2 *−R2 = 1/T2 *−1/T2 . R2 ′ was measured in MS white matter lesions and in regions of interest in normal appearing white matter (NAWM) and grey matter in all subjects. Results: R2 ′ was reduced in NAWM in MS compared with controls (9.5/s vs 10.1/s, p=0.05). R2 ′ was additionally reduced in lesions, both T1 isointense (8.5/s vs 9.5/s, p=0.02) and T1 hypointense (7.7/s vs 9.5/s, p=0.003) compared with NAWM. R2 ′ tended to be higher in the basal ganglia of MS patients compared with controls, and was significantly higher in the caudate nucleus in secondary progressive MS (12.9/s vs 10.9/s, p=0.03). Increased T2 lesion volume predicted an increase in R2 ′ in the caudate (β=0.412, p=0.02). Conclusions: Reduction in R2 ′ in NAWM and lesions is consistent with a decreases in myelin, tissue iron and/or deoxyhaemoglobin. Increased caudate R2 ′ in patients with secondary progressive MS is consistent with increased iron deposition, as corroborated by other techniques.